2008
DOI: 10.1097/prs.0b013e3181845931
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects and Radioprotection in MC3T3-E1 Mouse Calvarial Osteoblastic Cells

Abstract: This study reveals improved survival after irradiation in osteoblast-like cells treated with WR-1065 in vitro and corroborates previous findings from animal models. Further studies using this agent and similar drugs are important for devising strategies to prevent radiation-induced inhibition of craniofacial bone growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
2
13
0
1
Order By: Relevance
“…1C.). However, another study analyzed the effect of radiation on OPN levels in osteoblastic cells and found a slightly elevated expression of OPN on days 14 and 21 after irradiation [40]. …”
Section: Discussionmentioning
confidence: 99%
“…1C.). However, another study analyzed the effect of radiation on OPN levels in osteoblastic cells and found a slightly elevated expression of OPN on days 14 and 21 after irradiation [40]. …”
Section: Discussionmentioning
confidence: 99%
“…For SOD1 and GPx amplification [80], PCR conditions were 94°C for 2 minutes followed by 25 cycles of 94°C for 15 seconds, 57°C for 30 seconds, 72°C for 45 seconds annealing, and a final extension of 72°C for 10 minutes. Using methods described by Gevorgyan et al [81] OCN (bone Gla protein) was amplified using 94°C for 2 minutes followed by 25 cycles of 94°C for 1 minute, 58°C for 45 seconds, 72°C for I minute annealing, and a final extension of 72°C for 10 minutes. Similarly, secreted phosphoprotein 1(OPN) was amplified using 94°C for 2 minutes followed by 18 cycles of 95°C for 1 minute, 55°C for 2 minutes, 72°C for I minute annealing, and a final extension of 72°C for 10 minutes [81].…”
Section: Methodsmentioning
confidence: 99%
“…Using methods described by Gevorgyan et al [81] OCN (bone Gla protein) was amplified using 94°C for 2 minutes followed by 25 cycles of 94°C for 1 minute, 58°C for 45 seconds, 72°C for I minute annealing, and a final extension of 72°C for 10 minutes. Similarly, secreted phosphoprotein 1(OPN) was amplified using 94°C for 2 minutes followed by 18 cycles of 95°C for 1 minute, 55°C for 2 minutes, 72°C for I minute annealing, and a final extension of 72°C for 10 minutes [81]. The PCR products were electrophoresed in 2% agarose gels.…”
Section: Methodsmentioning
confidence: 99%
“…Their study revealed AMF radioprotection with significant improvement of osteoblast-like cell survival. 31 Yurut-Caloglu et al studied the left femora of Wistar albino rats, which they irradiated at a single dose of 20 Gy following AMF pre-treatment. Their histopathological analysis of bone and cartilage revealed a significant reduction in radiation-induced bone and epiphysial cartilage damage in the AMF pre-treated specimens compared to irradiated specimens alone.…”
Section: Discussionmentioning
confidence: 99%